Varieties of clean energy transitions in Europe: Political-economic foundations of onshore and offshore wind development - Stefan Ćetković; Aron Buzogány; Miranda Schreurs (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The paper introduces a novel framework for classifying different types of national political economies. It applies the outlined framework to analyse in an historical perspective the development of one mature renewable energy sector (onshore wind) and one infant renewable energy sector (offshore wind) across three major types of European economies. The paper shows that the presence of strategic state-market coordination and the decentralized pluralist polity constitute key enabling factors that drive the development of new renewable energy technologies. The commonalities and differences in the political economy of the onshore and offshore wind sectors are also discussed.
Keywords: O25; O38; O33; 330; onshore wind; offshore wind; green industrial development; energy transition; varieties of capitalism